Precision Test of Glucose Levels Using the Enzymatic GOD-PAP Method with Serum and Plasma Samples - Sri Raviani; Arifiani Agustin Amalia; Chairil Anwar (Jurnal Kesehatan Cendikia Jenius, 2025)
Precision is an important parameter to assess the quality of an analytical method. Precision is related to how close individual test results are to the mean value in the same test. The general objective of this study was to determine the precision test results of glucose levels using the enzymatic GOD-PAP method with serum and plasma samples. The research design applied in this study was descriptive quantitative with an experimental approach using primary data. The population in this study consisted of TLM students at Universitas ‘Aisyiyah Yogyakarta, class of 2021 and 2023, with a total of 39 respondents. The glucose level test results of serum and plasma samples were processed using Microsoft Excel to obtain the mean and standard deviation (SD), followed by calculating the coefficient of variation (CV%) as a precision indicator. The results showed that the coefficient of variation (CV%) for serum samples met the CV% requirement (≤5%) for all data, with the highest CV% value of 0.599% and the lowest of 0.000%. Similarly, plasma samples also showed that all data met the CV% requirement (≤5%), with the highest CV% value of 1.469% and the lowest of 0.000%. The conclusion of this study indicates that the precision of serum and plasma samples was considered good and acceptable since it complied with the blood glucose CV% limit set by the Indonesian Ministry of Health (≤5%). Further research is recommended to increase the sample size, compare with other methods, and use more advanced statistical software to enhance result validity.